2021
DOI: 10.1177/23259671211043097
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors Influencing Functional Results After Proximal Hamstring Tendon Avulsion Surgery: A Patient-Reported Outcome Study After 227 Operations From a Single Center

Abstract: Background: Although debilitating, proximal hamstring tendon avulsion injuries are rare and often overlooked or misdiagnosed. Consequently, delayed diagnosis and surgical treatment may result in poor outcomes. Studies investigating a correlation between postoperative functional outcomes and this delay in surgical treatment or other concomitant factors in large cohorts have not yet been performed to our knowledge. Purpose/Hypothesis: The purpose of this study was to conduct an investigation in a large patient g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(122 reference statements)
2
5
0
Order By: Relevance
“…The subjective satisfaction rate in our patients was extremely high and comparable to non-modified hamstring refixation (98.8 vs. 97% [19]). Similarly, the PHAT score was comparable to what was reported for patients after other surgical refixation methods (78.8 vs. 74.1 [41], 79.8 [42] and 79.9 [43]). The questions with the lowest points in the PHAT were number of minutes without discomfort while driving a car, number of minutes without discomfort while running and description of the current level of activity.…”
Section: Discussionsupporting
confidence: 79%
“…The subjective satisfaction rate in our patients was extremely high and comparable to non-modified hamstring refixation (98.8 vs. 97% [19]). Similarly, the PHAT score was comparable to what was reported for patients after other surgical refixation methods (78.8 vs. 74.1 [41], 79.8 [42] and 79.9 [43]). The questions with the lowest points in the PHAT were number of minutes without discomfort while driving a car, number of minutes without discomfort while running and description of the current level of activity.…”
Section: Discussionsupporting
confidence: 79%
“… 16 Additionally, the PHAT is the most frequently used of these proximal hamstring–specific PROMs in the literature (6/34 included studies) and has been gaining recognition as the preferred PROM for proximal hamstring injury studies. 2 , 3 , 7 , 8 , 26 , 27 , 33 In conjunction with these findings, the PHAT had the greatest proportion of unique questions compared with the other proximal hamstring–specific PROMs in this study. These unique questions incorporate a visual analog scale to evaluate pain “at rest” and “with stride-out stretch” as well as categorical scores for activity levels, such as the maximum time for “driving a car.” 8 Moreover, the PHAT contextualizes common symptoms and characterizes the potential sequelae of proximal hamstring injuries, such as gluteal pain and sitting intolerance, more comprehensively than the questions in the SHORE.…”
Section: Discussionsupporting
confidence: 68%
“…Bowman et al 8 reported a similar conclusion based on 45 patients at a minimum 1-year follow-up, as they were unable to detect any significant difference in outcome scores between tear grades. Likewise, in 204 full-thickness tears, Best et al 6 reported that the amount of stump retraction (>5 cm) did not significantly influence outcome scores at short-term follow-up. However, Barnett et al 5 reported after analyzing their cohort of 132 patients that those with complete tears and acute surgical treatment were more likely to have a good or excellent result than those with partial-thickness tears at a 2-year follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, there are limited and inconsistent data on the effect of preoperative patient factors and tendon characteristics, such as tear size and tendon retraction, on postoperative outcomes to help guide the approach for the treatment of different tears. 5,6,8,21,35 Moreover, the relative indications for open and endoscopic repair have yet to be elucidated, and the literature does not clearly support one over the other in most outcomes. 2 The purposes of this study were to (1) report on achievement rates of clinically significant outcomes at a minimum 2-year follow-up for multiple patient-reported outcomes (PROs) after surgical treatment of proximal hamstring injuries, stratified according to severity of proximal hamstring injury, and (2) report on how tear characteristics are associated with PROs and the achievement of clinically significant outcomes after endoscopic and open surgical repair.…”
Section: -In-5mentioning
confidence: 99%
See 1 more Smart Citation